PERAN GURU SEBAGAI FASILITATOR DALAM PENGELOLAAN KELAS UNTUK ANAK BERKEBUTUHAN KHUSUS DI SDN 138/X RANTAU RASAU - Julita Tantri; Mulyadi Mulyadi; Linardo Pratama (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
This research is motivated by the demand for effective classroom management in the context of heterogeneous classes involving children with special needs (ABK) in regular elementary schools, while teachers still face various limitations in its implementation. This study aims to describe the role of facilitator teachers in inclusive classroom management, identify the challenges faced by teachers, and explain the efforts made to overcome these challenges at SD Negeri 138/X Rantau Rasau. This study uses a qualitative approach with a descriptive research type and a phenomenological approach. The research subjects consisted of five class teachers and one principal who were selected purposively based on their direct involvement in learning involving ABK. Data collection techniques included in-depth interviews, observation, and documentation to obtain comprehensive data. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the role of teachers as facilitators is reflected in non-discriminatory learning interactions, adaptive classroom environment arrangement, flexible management of learning flows, and adjustments to learning strategies according to student needs.